2020
DOI: 10.21203/rs.3.rs-120616/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Predicting Response to Total Neoadjuvant Treatment (TNT) in Locally Advanced Rectal Cancer Based on Multiparametric Magnetic Resonance Imaging: A Retrospective Study

Abstract: Purpose: To investigate the potential value of magnetic resonance imaging (MRI) in predicting response relevance to total neoadjuvant treatment (TNT) in locally advanced rectal cancer.Methods: We analyzed MRI of 71 patients underwent TNT from 2015 to 2017 retrospectively. We categorized the response of TNT as CR (complete response) and non-CR, and high, moderate and low sensitivity. Logistic regression analysis was used to identify the best predictors of response. Diagnostic performance was assessed using rece… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 36 publications
1
0
0
Order By: Relevance
“…Identifying these features can help the multidisciplinary team identify the appropriate neoadjuvant, adjuvant, and surgical plans. 6,21,22 We found that nCRT was independently associated with positive CRM; this has been described previously and is likely attributed to selection bias of locally advanced disease for nCRT or tumors resistant to therapy with poor downstaging. 3 It may also reflect compliance with nCRT recommendations, which is complex and multifactorial, 23,24 and the patient understanding of their treatment options, a difficult variable to measure that can contribute to nCRT use and subsequent outcomes, including CRM rate.…”
Section: Discussionsupporting
confidence: 82%
“…Identifying these features can help the multidisciplinary team identify the appropriate neoadjuvant, adjuvant, and surgical plans. 6,21,22 We found that nCRT was independently associated with positive CRM; this has been described previously and is likely attributed to selection bias of locally advanced disease for nCRT or tumors resistant to therapy with poor downstaging. 3 It may also reflect compliance with nCRT recommendations, which is complex and multifactorial, 23,24 and the patient understanding of their treatment options, a difficult variable to measure that can contribute to nCRT use and subsequent outcomes, including CRM rate.…”
Section: Discussionsupporting
confidence: 82%